PERANAN SATUAN RESERSE KRIMINAL KEPOLISIAN RESOR KOTA PEKANBARU DALAM MENANGGULANGI TINDAK PIDANA PENADAHAN KENDARAAN BERMOTOR DI KOTA PEKANBARU - IVAN SILABAN; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Reservior has encouraged others to commit crimes, it does not, if no one is willing to accept the proceeds of crime. If this can't be fixed of course like any society very disturbing feat. Then this is the role of the police force in tackling crime reservior is indispensable because the criminal action have trasnasional reservior is made with a "modus operandi" advanced technology, and supported by the organization. Therefore law enforcement agencies especially the Police Department Criminal Reserse expected to address and provides penindakan in accordance with the regulations to the perpetrators of criminal acts, to improve the comfort of the reservior, prosperity among the people.In accordance with the explanation above, the authors are interested in doing research with the title role of criminal police unit Reserse Resort Pekanbaru in tackling crime Reservior motor vehicle in the city of Pekanbaru. Where this thesis aim here, the first one to know the role of the police in addressing and overcoming the evil Criminal Reservior Reserse in Pekanbaru police resort. The second obstacle to find out what happened to the Police Resort town of Pekan Baru.Third attempt to find out what was done by the police in this Resort City of Pekanbaru. This type of research in sociological research classify types of juridical, for penenelitian the author of research directly on a location or place that is examined to provide a complete and clear picture of the problems in accurate. This research was conducted in the city of Pekanbaru Polres especially in the Unit, while the population of Reserse criminal and samples from all the parties concerned with issues that are examined in this study, the data source using the data, secondary data, and the data tertier, the primary data gathered in this study with interviews, kusioner, and the study of librarianship.The results of the discussion in this study is the role of the Criminal Police Unit Reserse Resort Pekanbaru in handling crime reservior in the city of Pekanbaru, where in the process of tackling financial crime police unit reservior role in preventative and repressive. Prevention activities carried out patrol and legal guidance on societies, and repressive activities do Criminal Police Unit another Reserse education do the observation, arrest, Search, seizure and anchoring. Then the head of the Criminal Police Unit in realizing the shelter and Community Services expected are ussually consistent in terms of Prefentif and repressive.Keywords : Roles – Law Enforcement – Criminal act Reservior.